POLITIK KEKERABATAN AGUS AMBO DJIWA PADA PEMILUKADA KABUPATEN PASANGKAYU TAHUN 2020 - Rusmawaty Rusdin (Journal Publicuho, 2021)
One study that is interesting to discuss is the political kinship established by the Agus Ambo Djiwa clan. Agus Ambo Djiwa has played an important role in Pasangkayu politics in building politics since 2005 to become deputy regent and then to regent two for the 2010-2020 period. Now he has successfully led his brother and wife to become regents and deputy regents of Pasangkayu in the 2021-2024 period. The purpose of this study was to determine the modalities of Agus Ambo Djwa's kinship politics in winning the political event in Pasangkayu. This study uses a qualitative method. Data collection techniques using observation, interviews, and documentation studies. Data analysis used the Miles and Huberman model, namely data collection, data reduction, data presentation and verification. The results showed that there was an inheritance of leadership politics in Pasangkayu which was after the expansion of the Mamuju district. The Agus Agus Djiwa clan won the 2020 elections because it has four basic material modalities, namely the Ambo Djiwa Family social capital, which is one of the figures in the formation of the division of North Mamuju Regency which is currently known as Pasangkayu and Agus Ambo Djiwa still in control of the regional bureaucracy, cultural capital relying on family names and politics ethnic identity, political capital supported by political parties and economic capital originate from personal wealth and donations from donors.